The image of the Islamic Republic of Iran in the independent Iraqi press: An analytical study of the Al—Zaman, Al-Dustour, and Al-Mada newspapers - Hassan, Hossam Habib; Dabkh, Widad Ghazi (ALBAHITH ALALAMI, 2022)
Through this descriptive study of the image of the Islamic Republic of Iran in the independent Iraqi press, the researcher relies on surveys, content analysis, and observation tools. The research community selected was the Iraqi independent press, represented by the Al-Zaman, Al-Dustour, and Al-Mada newspapers. The researcher adopts the comprehensive inventory method for newspaper issues produced between October 2019 and January 2020. The results of this study show that Iran’s interference in Iraq’s internal affairs was one of the most prominent components of the picture that independent Iraqi newspapers seek to paint about the Islamic Republic of Iran.